Using Molecular Modelling Tools to Understand the Thermodynamic Behaviour of Ionic Liquids - Vega, Lourdes F.; Vilaseca, Oriol; Valente, Edoardo; Andreu, Jordi S.; Llovell, Fèlix; Marcos, Rosa M. (IntechOpen, 2011)
None